2018
DOI: 10.19044/esj.2018.v14n9p143
|View full text |Cite
|
Sign up to set email alerts
|

Analyse De L'efficacité Technique Des Exploitations Agricoles Familiales À Maurice

Abstract: This study was undertaken to determine the technical efficiency of family farms and to identify the factors which determine their productivity. All in all, 200 farmers were randomly selected and interviewed using a structured questionnaire to obtain data on agricultural production and input use during 2014. The Data Envelopment Analysis (DEA) technique was used to determine the levels of technical efficiency of such enterprises. Besides, a Tobit regression model was applied to identify the factors influencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…It was close to the average reported by Freud et al (1997) for the period from 1994 to 1996, when they estimated it at 500 kg.ha − 1 of unshelled grains for the department of Fatick. It was also close to the average yields of 504 and 506 kg.ha − 1 reported by Faye et al (2019) for farms located in various regions of the groundnut basin, and close to the average yield of 683 kg.ha − 1 reported by Ndiaye (2018) for Kaolack region in 2017. According to Lericollais (1972) in the Niakhar observatory, it was lower than in 1965 and 1967, when annual rainfall amounted 560 and 729 mm respectively, but it was higher than in 1966 and not signi cantly different from 1968 and 1969, when annual rainfall amounted 807, 335 and 711 mm respectively (Fig.…”
Section: Groundnut Yields and Indicators Of Socio-economic Performanc...supporting
confidence: 85%
“…It was close to the average reported by Freud et al (1997) for the period from 1994 to 1996, when they estimated it at 500 kg.ha − 1 of unshelled grains for the department of Fatick. It was also close to the average yields of 504 and 506 kg.ha − 1 reported by Faye et al (2019) for farms located in various regions of the groundnut basin, and close to the average yield of 683 kg.ha − 1 reported by Ndiaye (2018) for Kaolack region in 2017. According to Lericollais (1972) in the Niakhar observatory, it was lower than in 1965 and 1967, when annual rainfall amounted 560 and 729 mm respectively, but it was higher than in 1966 and not signi cantly different from 1968 and 1969, when annual rainfall amounted 807, 335 and 711 mm respectively (Fig.…”
Section: Groundnut Yields and Indicators Of Socio-economic Performanc...supporting
confidence: 85%
“…These inefficient farms, therefore, have room to improve their performance [3]. They will be able to refer to technically efficient farms to apply their best practices [4]. According to Gunther and Chauveau (2002), quoted by Ben Nasr et al, "this approach is particularly suitable for measuring the efficiency of firms combining several inputs to produce several outputs" [5].…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…The use of the TOBIT model for the analysis of determinants has shown that cocoa farming as main activity, acquiring land by inheritance or gift, marital status, producer age, and farm age impact technical efficiency positively. Ndiaye (2018) analyzed the technical efficiency of family farms in Mauritius. The nonparametric Data Envelopment Analysis (DEA) approach and the TOBIT model were used to measure effectiveness and identify its determinants.…”
Section: Analysis Of Determinants Of Technical Efficiencymentioning
confidence: 99%